Mapping the spatial distribution of poverty using satellite imagery in the Philippines. - Asian Development Bank (Manila,Philippines Asian Development Bank, [2021])
The leave no one behind principle of the 2030 Agenda for Sustainable Development requires appropriate indicators for different segments of a country population. Conducted by ADB in collaboration with the Philippine Statistics Authority and the World Data Lab, the study aimed to enhance the granularity, cost effectiveness, and compilation of high quality poverty statistics in the Philippines.
Keywords: Energy economics -- Cost effectiveness; Sustainable development -- Philippines; Poverty -- Philippines; Electronic book